Model‐Informed Drug Development Approaches to Assist New Drug Development in the COVID‐19 Pandemic. Issue 3 (4th December 2021) - Xiong, Ye; Fan, Jianghong; Kitabi, Eliford; Zhang, Xinyuan; Bi, Youwei; Grimstein, Manuela; Yang, Yuching; Earp, Justin C.; Zheng, Nan; Liu, Jiang; Wang, Yaning; Zhu, Hao
Abstract : Leveraging limited clinical and nonclinical data through modeling approaches facilitates new drug development and regulatory decision making amid the coronavirus disease 2019 (COVID‐19) pandemic. Model‐informed drug development (MIDD) is an essential tool to integrate those data and generate evidence to (i) provide support for effectiveness in repurposed or new compounds to combat COVID‐19 and dose selection when clinical data are lacking; (ii) assess efficacy under practical situations such as dose reduction to overcome supply issues or emergence of resistant variant strains; (iii) demonstrate applicability of MIDD for full extrapolation to adolescents and sometimes to young pediatric patients; and (iv) evaluate the appropriateness for prolonging a dosing interval to reduce the frequency of hospital visits during the pandemic. Ongoing research activities of MIDD reflect our continuous effort and commitment in bridging knowledge gaps that leads to the availability of effective treatments through innovation. Case examples are presented to illustrate how MIDD has been used in various stages of drug development and has the potential to inform regulatory decision making.